SOCIAL INNOVATION IN ENGINEERING EDUCATION - Ahrens, Andreas; Zaščerinska, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Traditionally, engineering students are provided with new knowledge by educatorstudent interaction based on educator’s academic (social) knowledge or student-student interaction based on their practical (individual) knowledge. That is why engineering students lack the inter-connection between the academic and practical knowledge. However, engineering education should lead to the transformation of students’ knowledge from external (social) to internal (individual) perspective. Social innovation that has become the dominant response to challenges in all the domains of modern life includes peer-learning as the subphase to create socially shared knowledge in the transformation of students’ knowledge from external to internal perspective and Enterprise 3.0 as a component of social media integrated into the teaching and learning process. This allows the novel transformation of students’ knowledge from external to internal perspective, as introduced in this contribution, that proceeds from teaching through peer-learning to learning to be integrated in the environments of engineering education.